PENGARUH TOKSOPLASMOSIS TERHADAP PENAMPILAN REPRODUKSI SAPI BETINA - , FLORENTINA BETY INDAH L., drh. Agung Budiyanto, MP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of the research was to study the effect of toxoplasmosis on reproductive performance in cattle, include estrous cycle, estrous periode, estrous post partus, service per conception (S/C), and calving interval (CI). A number of 5cc blood sample per each was collected from 31 cattle from jugular vein or coccigeal vein, than to be waited until the serum formed. Toxoplasmosis was checked in serum by Pastorex Toxo. Reproductive performance have been collected by questioner method. The reproductive performance data of seropositive and seronegative toksoplasmosis cattle were analysed descriptively. The result of reproductive performance from seropositive toxoplasmosis showed estrous cycle 21 days, estrous periode 34 hours, estrous post partus 80 hours, service per conception (S/C) 3,5 times, and calving interval (CI) 17,5 months, and than from seronegative toxoplasmosis showed estrous cycle 23,48 days, estrous periode 33,52 hours, estrous post partus 84,48 hours, service per conception (S/C) 2,55 times, and calving interval (CI) 15,55 months. This research indicated that the cattle with toxoplasmosis have no correlation with their reproductive performance.